Mexico’s 2017 Educational Model of Secondary Education: A Review from the Lens of the Teaching of English in Tele-secondary schools - Hernández Hernández, Miguel (Emerging Trends in Education, 2019)
The present review relies on the inclusion of English Language Teaching in the curriculum of the tele-secondary modality. The implementation of the national curriculum and its strategies show that the tele-secondary school system appears left out, or at least, left behind. This review shows concerns that raise questions for the teaching of ELT in tele-secondaries although ELT has been included in this educational option since its beginning. Thus, it seems that results have not been achieved at all. Even though it is true that the National Program of English is a good opportunity to improve the level of English at the secondary level. It seems to be that ELT is constrained to support generalist teachers.